Development of an algorithm to estimate soaking posture in the bathwater - Ryota NAKAMURA (The Japan Society of Mechanical Engineers, 2019)
Soaking in bathwater has been a familiar custom for the Japanese for a long period of time. The authors discussed bathing comfort from the viewpoint of biomechanics in a previous study. However, it took a lot of effort to evaluate the joint torques during soaking in the water while conducting the experiments. Therefore, it was required to estimate the soaking postures and center of pressure (COP) in order to conduct the biomechanical evaluation with minimal experiments. The objective of this research was to develop an algorithm to estimate soaking posture and COP. In this study, it was assumed that a human took a soaking posture in the bathtub so as to minimize muscle exertion, that is, to minimize the joint torque as much as possible. Based on this assumption, an algorithm to estimate the soaking posture was constructed as an optimization problem of the objective function. An experiment was conducted for the purpose of validating the estimation algorithm. In this experiment, three kinds of bathtub shapes were tested for five healthy males. As a result, the estimated posture and COP were in good agreement with the measured one. The maximum error of the joint angle was 6.0% among all participants. The average values of the error in the location of the COP for each condition were 0.01 m or less. From the results of the present study, the possibility of estimation the joint torque is suggested.